2018
DOI: 10.18203/2320-6012.ijrms20181428
|View full text |Cite
|
Sign up to set email alerts
|

Study of anaemia in type 2 diabetes mellitus

Abstract: Background: Anaemia is increasingly recognized entity in the patients with diabetes mellitus and constitutes an additional burden in patients. The prevalence of anaemia in the patients with diabetes is two or three times higher than in patients with comparable renal impairment and iron stores in the general population. As India is foreseen a diabetic capital of the world, it becomes imperative to recognize co-morbidities such as anaemia at the earliest. Hence this study is being conducted with the aim to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
4
7
0
Order By: Relevance
“…We observed that anemia has no signification with gender, as males were more than females (5.5% & 3.4%), as in table 2. Similarly, this agrees with previous study (Kaushik et al, 2018), that showed that males were more than females (68.25 % & 31.74 %) respectively, and this disagrees with another study (Rathod et al, 2016) (Hussain et al, 2010).…”
Section: Resultssupporting
confidence: 87%
“…We observed that anemia has no signification with gender, as males were more than females (5.5% & 3.4%), as in table 2. Similarly, this agrees with previous study (Kaushik et al, 2018), that showed that males were more than females (68.25 % & 31.74 %) respectively, and this disagrees with another study (Rathod et al, 2016) (Hussain et al, 2010).…”
Section: Resultssupporting
confidence: 87%
“…22 Some more studies done by Kaushik et al, Sajid et al and Pathak et al, reported 63%, 35.2% and 45.2% as their prevalence respectively. [23][24][25] The prevalence of our study was in concordance with many other studies conducted across the world. Urgent attention to screening of anaemia is required in the patients with type 2 diabetes which will further assist in early diagnosis and management of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…69,70 40% 44% However, this study deviates from another study conducted in India, which showed a higher rate of the microcytic hypochromic type of anemia. 71 The low prevalence of microcytic hypochromic anemia in this study could be explained by their residence and access to health care services. In this study, closer to three-fifth of the participants were from urban areas where health care services related to appropriate nutrition and a variety of nutrition accessible.…”
Section: Discussionmentioning
confidence: 70%